Effects of media coverage on self-stigmatization, self-esteem, and affectivity in persons with depression = Auswirkungen von medialer Berichterstattung auf Selbststigmatisierung, Selbstwert und Affektivität bei Personen mit Depression - Göpfert, Nele Cornelia (Universitätsbibliothek Heidelberg, 2022)
Depression is a leading cause of ill health and disability. More than 300 million people worldwide and four million people in Germany are living with depressive symptoms. Depression can be treated effectively. Yet, one main barrier to take up professional support is stigmatization and self-stigma. Self-stigma in turn is positively related to suicidal behavior and negatively related to protective factors such as professional help-seeking and self-esteem. Therefore, self-stigma should be reduced. There is an ongoing debate about the impact of news with potentially stigmatizing content on people with depression. Against this background, one pre-study and two main studies aimed at building an empirical foundation for future evidenced based practice concerning media coverage and stigmatization of people with mental illness, i.e., depression. At first, an appropriate instrument for measuring the current level of self-stigma of people with depressive symptoms was required. The original 16-item Self-Stigma of Depression Scale was developed to measure anticipated self-stigma hypothetically in case of depression. In clinical samples, measuring actual experienced instead of hypothetical self-stigma may be more appropriate. Therefore, a pre-study aimed at changing all 16 items into German indicative and testing factor structure, internal consistency and construct validity in two independent clinical samples (nA=550; nB=180). The original structure of four factors (representing Shame, Self-Blame, Help-Seeking Inhibition, and Social Inadequacy) could be replicated in exploratory factor analyses with the exception of one item in Sample A. In Sample B, this empirically derived structure indicated a better fit than the alternatively tested original factor structure. Internal consistencies of subscales were satisfying to very good. Controlled for current depressive symptoms, there were significant correlations to self-esteem and other self-stigma scales as expected, supporting the construct validity. The adapted Self-Stigma of Depression Scale appears to be a valid and reliable scale for experienced self-stigma of people with depression. It therefore can be used in clinical samples to identify correlates, test theoretical models and the effectiveness of interventions. Second, a theoretical model of self-stigma specifically for people with depressive symptoms was tested in Study 1. The progressive model of self-stigma describes four stages of internalizing stereotypes of mental illness: Stereotype awareness, personal agreement, self-concurrence, and harm-to-self, i.e., self-esteem. The aim of Study 1 was to test the procedural character of the progressive model of self-stigma by one serial mediation model in two independent samples of people with at least one pre-diagnosed depressive episode or dysthymia. A cross-sectional computer-based survey was conducted in one online sample (nA=550) and one clinical face-to-face sample (nB=180). The PROCESS procedure for SPSS Version 3.00 was used for mediation analyses. The results support the progressive model of self-stigma in people with depression in most respects. Endorsements for stereotype awareness were higher than for personal agreement and self-concurrence; no relevant difference was found between personal agreement and self-concurrence. Successive stages had the strongest associations, with the exception of the association between stereotype awareness and self-esteem, which was higher than the association between stereotype awareness and personal agreement and self-concurrence. The association between stereotype awareness and self-esteem was partially mediated via personal agreement and self-concurrence. In sum, the progressive model of self-stigma offers a theoretical foundation for the process research of self-stigma. Study 2 applies the progressive model of self-stigma and gives insights into direct effects of potentially stigmatizing media reporting on people with depression, namely changes in levels of stigma stages, positive and negative affect, and self-esteem. In an experimental controlled trial of 180 patients with a clinical diagnosis of depressive episode or dysthymia, participants watched a short film on either a negative event relating to depression (experimental group), about a negative event without relation to depression (control group 1), or about a neutral event relating to depression (control group 2). General linear models with repeated-measures and one-way ANOVAs of the change in scores, followed by Bonferroni-adjusted pairwise comparisons using IBM SPSS Statistics 24.0, indicated significant group × time interactions in stereotype agreement and negative affect. As such, even single short film presentations of familiar events that contain stigmatizing content increase the level of stigma measures (i.e., stereotype agreement) and negative affect in stigma carriers. Nevertheless, longitudinal research on and long-term exposure to media coverage is needed to investigate predictive effects, consequences and potential interventions on people with depression, considering different stages of stigma separately for a deeper understanding of self-stigma processes.